2022
DOI: 10.31590/ejosat.1038595
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electric Arc Furnace Slag as an Additive in Biogas Production and Its Effects

Abstract: Anaerobic digestion (AD) is a biological process in which organic wastes are converted into gases such as CH4, CO2, and H2S by microorganisms. In AD, using additives is a widespread approach to improve the anaerobic environment of microbial communities, increase microorganisms' activity, and provide more biogas production. This study investigates the effects of adding the electric arc furnace slag (EAFS) as an additive to the AD system on biogas and methane production. EAFS was obtained from a company that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Previously, slag was used for construction, which underutilizes its resource potential and may cause secondary pollution. Recently, Çalhan et al (2022) [88] reported slag as a good additive in AD, as it enhances the production of biogas, stabilizes digesters, reduces COD as well as inhibitors, and improves the digestates' properties. The produced biogas can be polished to generate methane for electricity and heat, while the digestates will be used as soil conditioner.…”
Section: Treatment Of Discarded Photovoltaic Solar Panels Under Plasm...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, slag was used for construction, which underutilizes its resource potential and may cause secondary pollution. Recently, Çalhan et al (2022) [88] reported slag as a good additive in AD, as it enhances the production of biogas, stabilizes digesters, reduces COD as well as inhibitors, and improves the digestates' properties. The produced biogas can be polished to generate methane for electricity and heat, while the digestates will be used as soil conditioner.…”
Section: Treatment Of Discarded Photovoltaic Solar Panels Under Plasm...mentioning
confidence: 99%
“…Producing slag through DSP plasma pyrolysis will increase the supply in the market, potentially reducing costs. Additionally, many researchers have reported the utilization of slag as an additive to stabilize and improve AD treatment [88]. The slag enhances the production of biogas from AD, with methane and carbon dioxide as major constituent gases, which can be upgraded to generate energy, heat, and electricity.…”
Section: Techno-economic Performance Of Discarded Photovoltaic Solar ...mentioning
confidence: 99%